Ludzie (z) Nowej Huty. O dwóch filmach Kazimierza Karabasza - Zwierzchowski, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
The People of Nowa Huta. Two films by Kazimierz Karabasz Nowa Huta, a symbol of a generation and significant place in the symbolic space of the Polish People’s Republic, was a character in newsreels, documentaries and films many times. The latter include two films by Kazimierz Karabasz: Shadow is Not Far (1984) and Memory (1985). In them Nowa Huta forms a setting for stories told about common people, yet it is also an important setting that determines their place in life, both in the past and in the present, regardless of whether they feel attached to it or rebel against it. Karabasz s heroes were people from Nowa Huta. They built it, and worked and lived in it. They were also shaped by its building. They are therefore also the people of Nowa Huta.